1998
DOI: 10.1046/j.1365-2141.1998.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Human myeloma cell apoptosis induced by interferon‐α

Abstract: Although there have been reports regarding the clinical effectiveness of IFNα in the treatment of myeloma patients during this decade, its biological effects on human myeloma cells have still not been clarified. Recently, apoptosis has been considered as one of the most important mechanisms in the programmed cell death of malignant tumour cells induced by chemotherapeutic agents or cytotoxic immunological defence in malignancy‐carrying hosts. Among the several pathways which function to induce apoptosis, Fas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Type I-IFN has also been shown to promote apoptosis in several tumor cell lines in vitro, including multiple myeloma and acute lymphoblastic leukemia. [41][42][43] Together with the in vivo data presented here, this provides a rationale for studying the expression of the type I-IFN receptor on primary human hematopoietic malignancies. In receptor-positive malignancies, the administration of type I-IFN after BM transplantation may augment the sensitivity of residual malignancy to GVL responses and may be worthy of study in patients at very high risk or relapse (eg, myeloma, primary refractory acute myeloid leukemia).…”
Section: Discussionmentioning
confidence: 99%
“…Type I-IFN has also been shown to promote apoptosis in several tumor cell lines in vitro, including multiple myeloma and acute lymphoblastic leukemia. [41][42][43] Together with the in vivo data presented here, this provides a rationale for studying the expression of the type I-IFN receptor on primary human hematopoietic malignancies. In receptor-positive malignancies, the administration of type I-IFN after BM transplantation may augment the sensitivity of residual malignancy to GVL responses and may be worthy of study in patients at very high risk or relapse (eg, myeloma, primary refractory acute myeloid leukemia).…”
Section: Discussionmentioning
confidence: 99%
“…For conventional PCR, 1 L cDNA was amplified using 2.5 U Taq DNA polymerase (Takara Bio, Kusatsu, Japan), and for real-time PCR to detect the gene expression quantitatively, LightCycler reagents and instruments (Roche, Mannheim, Germany) were used according to the manufacturer's instructions. The sequences of the used primers for p21 Cip1/Waf1 (Ookawa et al 44 ) and bax 45 were described elsewhere. The primers for Fas ligand gene (sense, 5Ј-CCT CCA GGC ACA GTT CTT CC-3Ј; antisense, 5Ј-TAC CAA GGC AAC CAG AAC CA-3Ј) and for p27 Kip1 gene (sense, 5Ј-GGG GCT CCG GCT AAC TCT GA-3Ј; antisense, 5Ј-GGC TTC TTG GGC GTC TGC TC-3Ј) were also used for PCR.…”
Section: Rna Extraction and Reverse Transcription-polymerase Chain Rementioning
confidence: 99%
“…A review by the European Myeloma Research Network identified beneficial effects of IFNs in 3 randomized studies and no effect in 3 others (6). Depending on experimental conditions, IFNs can either stimulate or inhibit cell survival or induce apoptosis in myeloma cells (7)(8)(9)(10)(11). Induction of TRAIL (also known as Apo2L) has been proposed to mediate apoptosis induced by IFN-α in myeloma cells and in solid tumors (9,12,13).…”
Section: Introductionmentioning
confidence: 99%